Gut Microbiota: Therapeutic Targets of Ginseng Against Multiple Disorders and Ginsenoside Transformation - Chen, Zhaoqiang; Zhang, Zepeng; Liu, Jiaqi; Qi, Hongyu; Li, Jing; Chen, Jinjin; Huang, Qingxia; Liu, Qing; Mi, Jia; Li, Xiangyan (Frontiers in Cellular and Infection Microbiology, 2022)
Panax ginseng, as the king of Chinese herb, has significant therapeutic effects on obesity, type 2 diabetes mellitus, fatty liver disease, colitis, diarrhea, and many other diseases. This review systematically summarized recent findings, which show that ginseng plays its role by regulating gut microbiota diversity, and gut microbiota could also regulate the transformation of ginsenosides. We conclude the characteristics of ginseng in regulating gut microbiota, as the potential targets to prevent and treat metabolic diseases, colitis, neurological diseases, cancer, and other diseases. Ginseng treatment can increase some probiotics such as Bifidobacterium, Bacteroidetes, Verrucomicrobia, Akkermansia, and reduce pathogenic bacteria such as Deferribacters, Lactobacillus, Helicobacter against various diseases. Meanwhile, Bacteroides, Eubacterium, and Bifidobacterium were found to be the key bacteria for ginsenoside transformation in vivo. Overall, ginseng can regulate gut microbiome diversity, further affect the synthesis of secondary metabolites, as well as promote the transformation of ginsenosides for improving the absorptivity of ginsenosides. This review can provide better insight into the interaction of ginseng with gut microbiota in multiple disorders and ginsenoside transformation.